Analysis of drain current saturation behaviour in GaN polarisation super junction HFETs. Issue 14 (5th October 2018) - Unni, Vineet; Long, Hong Yao; Yan, Hongyang; Nakajima, Akira; Kawai, Hiroji; Sankara Narayanan, Ekkanath Madathil
Abstract : The magnitude of saturation current in a power device significantly impacts its short‐circuit capability. In conjunction with the unprecedented miniaturisation that gallium nitride (GaN) offers, there is a compelling rationale to examine this critical parameter in GaN transistors for thermally stable and reliable power converter applications. This study presents a comprehensive analysis of the physical behaviour that yields intrinsically low drain current saturation in GaN polarisation super junction heterojunction field‐effect transistors (PSJ HFETs). The analysis in this work has been performed using electrical characterisation data of conventional and PSJ HFETs, supported by physics‐based two‐dimensional device simulations. Insight is gained on the differing device architecture‐dependent mechanisms that determine the magnitude of drain current density in both types of devices when biased in the saturation region.